2007
DOI: 10.1080/00365510600987728
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of osteoprotegerin during normo‐ and hyperglycaemic clamping

Abstract: Acute hyperglycaemia does not seem to increase plasma levels of OPG in non-diabetic subjects, whereas hyperinsulinaemia may suppress plasma levels of OPG. This finding indicates that the elevated plasma levels of OPG observed in diabetic subjects with poor metabolic control cannot be ascribed to hyperglycaemia per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…In a previous study of acute effects of hyperglycemia, we found no effects on plasma OPG in a set-up very similar to the present, also using the same OPG assay (38). Thus, no variations seem to occur in plasma OPG during the time of the day, where these experiments are performed.…”
Section: Discussionsupporting
confidence: 84%
“…In a previous study of acute effects of hyperglycemia, we found no effects on plasma OPG in a set-up very similar to the present, also using the same OPG assay (38). Thus, no variations seem to occur in plasma OPG during the time of the day, where these experiments are performed.…”
Section: Discussionsupporting
confidence: 84%
“…Rasmussen et al [42] made a similar observation in patients with type 1 diabetes. Knudsen et al [53] have suggested that the elevated plasma levels of OPG observed in diabetic subjects with poor metabolic control cannot be ascribed to hyperglycaemia per se, a fact confirmed by other authors [36,60]. Oral glucose intake causes decreases in serum OPG levels in postmenopausal women, and this effect is attenuated in women with type 2 diabetes [57].…”
Section: Opg and Diabetesmentioning
confidence: 84%
“…In the following years, several authors confirmed the association between serum OPG and both types of diabetes [24,35,36,41,42,[49][50][51][52][53][54][55][56][57][58][59]. Galluzzi et al [41] showed that plasma OPG levels are significantly higher in prepubertal children with type 1 diabetes mellitus than in controls, and evidenced a correlation between OPG serum concentrations and glycated haemoglobin (HbA1c).…”
Section: Opg and Diabetesmentioning
confidence: 90%
“…During a hyperglycemic clamp study Knudsen et al showed that decreasing levels of OPG were negatively correlated with changes in insulin levels but not with changes in glucose concentrations, indicating that hyperinsulinemia may suppress OPG synthesis and/or release (33). Two recent in vitro studies have partly supported this theory, and have shown insulinsuppressed OPG synthesis in adipocytes and vascular smooth muscle cells (34,35).…”
Section: Opg Levels Declined After the Oral Glucose Loadmentioning
confidence: 99%